2008
DOI: 10.1007/s11661-008-9666-3
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization during Thermomechanical Processing of IMI834

Abstract: The microstructure development of the near-a titanium alloy IMI834 displaying an initial bimodal a + b microstructure has been characterized with respect to dynamic and static b recrystallization, through quantitative metallography. The investigation was supplemented by interrupted compression testing, to evaluate the applicability of fractional softening in the determination of static recrystallization kinetics for titanium alloys. Micrographs are presented that indicate that dynamic recrystallization occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…9(d)). Similar behavior has been previously reported for near-␣ IMI834 alloy [20] and ␣ + ␤ TC11 alloy [21], which has been attributed to the dynamic recrystallization of ␣ phases [21].…”
Section: Microstructures Of the Second-loading Regionsupporting
confidence: 88%
“…9(d)). Similar behavior has been previously reported for near-␣ IMI834 alloy [20] and ␣ + ␤ TC11 alloy [21], which has been attributed to the dynamic recrystallization of ␣ phases [21].…”
Section: Microstructures Of the Second-loading Regionsupporting
confidence: 88%
“…For many two-phase titanium alloys, reported apparent activation energy above ␤ transus temperature is close to the activation energy of self-diffusion in ␤ phase [14][15][16], indicating dynamic recovery dominates ␤ working [17]. Though dynamic recrystallization is often observed in ␤ working, the volume fraction is generally small [17][18][19][20]. However, ␤ recrystallization was greatly accelerated in (␣ + ␤) working.…”
Section: Microstructure After the First Loading Stepmentioning
confidence: 89%
“…Higher strain rates in high temperature single ␤ phase field are often in favor of grain refinement because the rising dislocation substructures are not easily homogenized by self-diffusivity of titanium due to the insufficient recovery time [36]. The temperature 100-150 • C higher than the T ␤ was also reported beneficial to forging [5,6,37]. Thus, it can be concluded that the best forging parameter for ascast ATI 425 titanium alloy is at a strain rate greater than 0.1 s −1 at 1150 • C as shown in Fig.…”
Section: Processing Mapmentioning
confidence: 99%